Money growth and inflation: a regime switching approach - Gianni Amisano; Gabriel Fagan (European Central Bank (ECB), 2010)
We develop a time-varying transition probabilities Markov Switching model in which inflation is characterised by two regimes (high and low inflation). Using Bayesian techniques, we apply the model to the euro area, Germany, the US, the UK and Canada for data from the 1960s up to the present. Our estimates suggest that a smoothed measure of broad money growth, corrected for real-time estimates of trend velocity and potential output growth, has important leading indicator properties for switches between inflation regimes. Thus money growth provides an important early warning indicator for risks to price stability.
Keywords: C11; C53; E31; 330; Bayesian inference; early warning; inflation regimes; Markov Switching model; money growth; time varying transition probabilities; Prognoseverfahren; Bayes-Statistik; Geldmenge; Inflation; Monetärer Indikator; Deutschland; Eurozone; Großbritannien; Kanada; USA